Analisis Hubungan Faktor Sosiodemografi dan Sosioekonomi Dengan Tingkat Kepatuhan Pengobatan Pasien Diabetes Melitus Tipe 2 di Puskesmas Damai Berdasarkan MMAS-8 - Nuurositha, Nuurositha; Wahyuni , Fitri Ayu; Erwina , Wiwi; Rahman , Rifazul Aulia (Journal of Pharmaceutical and Sciences, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic disease requiring long-term therapy. Patient adherence to medication plays a crucial role in preventing complications. Unfortunately, the level of medication adherence among T2DM patients remains suboptimal and is influenced by various factors, including sociodemographic and socioeconomic factors. This study aims to analyze the association between sociodemographic and socioeconomic factors and medication adherence in T2DM patients at Puskesmas Damai, Balikpapan City. A cross-sectional design was applied with total sampling of all T2DM patients at Puskesmas Damai meeting the inclusion criteria. The Morisky Medication Adherence Scale-8 (MMAS-8) questionnaire was used to assess medication adherence. Data were analyzed using univariate and bivariate methods, with chi-square tests for associations. Bivariate analysis showed that gender (p = 0.021) and age (p = 0.039) were significantly associated with medication adherence. Meanwhile, education level (p = 0.428), employment status (p = 0.865), and income (p = 0.836) were not significantly associated. Understanding the factors influencing patient adherence can inform the design of more effective interventions to improve medication adherence and treatment outcomes in T2DM patients.